MicroRNA-148a Suppresses the Proliferation and Migration of Pancreatic Cancer Cells by Down-regulating ErbB3. Issue 9 (October 2016) - Feng, Hui; Wang, Yalei; Su, Jiaojiao; Liang, Hongwei; Zhang, Chen-Yu; Chen, Xi; Yao, Weiyan
Abstract : Objectives: ErbB3 (HER3) has been associated with pancreatic cancer progression, but little is known about its regulatory mechanisms. We investigated whether microRNAs (miRNAs) regulate levels of ErbB3 in pancreatic cancer cells. Methods: We used bioinformatic analyses to search for miRNAs that can potentially target ERBB3. Furthermore, the biological consequences of the targeting of ERBB3 by miR-148a were examined by cell proliferation and migration assays in vitro. Results: We identified an inverse correlation between miR-148a and ErbB3 protein levels in pancreatic cancer tissue samples and cell lines. We identified that miR-148a directly recognizes the 3′-UTR of the ErbB3 transcript and regulates ErbB3 expression. We demonstrated that the repression of ERBB3 by miR-148a suppressed the proliferation and migration of pancreatic cancer cells. In PANC-1 pancreatic cancer cells, the repression of ErbB3 by miR-148a inhibited the phosphorylation of ERK1/2 and AKT, which eventually repressed the proliferation and migration of these cells. Conclusions: Taken together, the present study provides the first evidence that miR-148a plays a significant role in the suppression of pancreatic tumorigenesis via the inhibition of ErbB3 translation. Abstract : Supplemental digital content is available in the text.